الروح الديني لاتجاهات الرثاء في العصر الإسلامي (دراسة وصفية): Religious Spirit, lamentations trends in the Islamic Era(Descriptive Study) - Dr. Abdul Majeed Baghdadi; Dr. Ghulam Ahmad (MEI, 2023)
Era of Sadr al-Islam is that period extending from the mission of the Prophet Muhammad, may God bless him and grant him peace, until the last days of the Rightly-Guided Caliphs, which ended with the killing of the Emir of the Believers, the Caliph of Islam and Muslims, Ali Ibn Abi Talib, may God be pleased with him, in the year 40 of the Hijrah, and the lament remained a poetic purpose in That era, however, a new doctrine was introduced to it with a situation.The linguistic meaning of the lament is related to the deceased is originally a source of the verb (lamentable), so the deceased is said to be lamentable, his praise after death. Lamentation is a term in which the ancient Arab poets mean the benefits and effects of the deceased. As for the modernizers, they have praise for the deceased and the abundance of his traits. Dr. Muhammad Al-Moneim Al-Khafji says defining the lament is the crying and mourning of the dead and the display of agony for his separation and the sadness of his death during which he promised the generosity that the enemies take care of losing and praising his manners.